INCREASING THE STUDENTS’ SPEAKING ABILITY THROUGH BAMBOO DANCING METHOD - Amar Ma'ruf; Rika Rahim (Universitas Muhammadiyah Makassar, 2013)
The objective of this research was to find out the improvement of the students’ fluency and speaking fluency through bamboo dancing pairs and to find out the improvement of the students’ fluency in speaking through bamboo dancing pairs. The researcher used a class Action Research (CAR). The researcher had conducted two cycles, where each cycle consists of four meetings. It employed speaking test as the instrument. The number subject of the research is 24 students in class V11. A. The researcher took data of real from the school to know the students’ speaking fluency. The research findings indicated that the use of Bamboo dancing Method increased the students’ speaking fluency. From the Table 1 indicated that there was increase the students’ speaking fluency from cycle I to cycle II, whereas in cycle I the students’ achievement was 5.5 and in cycle II the students’ achievement was 7.2. Then from the table two indicated that there was increase the students’ speaking fluency from cycle I to cycle II, whereas in the cycle I the students’ achievement was 5.9 and in cycle II the students’ achievement was 7.8. From this findings, the research made a conclusion that by using Bamboo Dancing method could improve the students’ motivation in speaking fluency and make the students’ active to speak in a learning process.Keyword: Increasing, speaking, ability, bamboo, dancing, method